THE PHENOMENON OF RATIFYING REVISION OF THE KPK LAW: HOW INVESTOR REACTED? - Pratama, Versiandika Yudha; Devy, Happy Sista (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2021)
This research aimed to determine there are difference in average abnormal returns of companies in the Jakarta Islamic Index (JII) before and after phenomenon the revised Corruption Eradication Commission Act, which is on September 17th, 2019. This research use event study for method and the data in this study are secondary data in the form of stock price. Sampling technique uses purposive sampling method. Determined sampling technique, 27 companies were obtained as research samples. Tests conducted are one sample t-test and paired sample t-test. The result of the one sample t-test showed that the phenomenon of ratifying the revision of the KPK law becomes meaningful information to investors and investors show that reactions to these event. It showed by the result of significant and negative abnormal returns in the few day before and several days after phenomenon. The result of the second hypothesis testing indicate that there is no significant difference the average abnormal return before and after the ratification of revised Corruption Eradication Commission Act Keywords: Revision of KPK Law, Average Abnormal Return, Event Study